Pendampingan Pembuatan Blog Sebagai Media Kampanye Sosial Penyalahgunaan Zat Adiktif Pada BKR Kelurahan Kratonan, Kota Surakarta - A Anditha Sari (Jurnal Pengabdian Pada Masyarakat, 2016)
Growth in the use of drugs actually not only in big cities but almost uniformly in a rural area of ​​the district to. Seeing these conditions, not only the government whose role is to make the handling but also the whole society should be concerned about the conditions in the vicinity. motivation for parents accompany their children to provide understanding and knowledge, motivation for teachers in schools to approach educates students so as not to lose the identity that ultimately are vulnerable, and the motivation of the residents in the neighborhood to come give attention among citizens so that the situation and environmental conditions remain conducive. Surakarta is consists of five districts based on reports BNN Surakarta as the first drug abuse-prone city in Central Java. This is supported by the demographic situation is increasingly. One of overpopulated area is district Kratonan. Aware of these threats Kratonan districts have a place for families and teens that BKR Group. Activities that are often carried out this group is counseling assistance in the form of free sex and drug abuse by peers. BKR is still active in activism, so it is important to providing media interactive between board members that blog. Through training blog creation targets were achieved outcomes Board has interactive media to target audiences about drugs and the impact of its misuse for the body. This training is divided into two stages: (1) Extension dangers of drugs by BNK Sukoharjo; (2) Explanation and simulation of blog creation.